XTM User manual for administrators, project managers, linguists & customers (Hedgerley Lane, 2020)
This document is an XTM user manual for both the complete standalone version of XTM called XTM Suite and the software as a service version called XTM Cloud.
Keywords: Linguistics.,Ngôn ngữ học